Efektivitas Terapi Kognitif Perilaku dalam Menangani Kecemasan pada Remaja - M. Alfazakki Ulil A; Hasby Rahmad H; Ferry Raya Eka (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Anxiety is a natural response that individuals may experience in response to situations that are perceived as potentially dangerous or threatening. It can be described as a state of apprehension or worry about the possibility of something undesirable happening. Adolescence is a transitional period filled with physical, emotional, and social changes, making it a stressful time. At this age, adolescents are not only developing physically, but also building their social and emotional identities. This study uses a library research approach, which is a research method carried out through tracing, reviewing, and analyzing relevant scientific literature sources. The results of this study indicate that cognitive therapy has been shown to play an important role in reducing anxiety levels in adolescents. This approach is a form of therapy that focuses on changing the way individuals think to influence their behavior and emotional responses. The purpose of this study was to determine the effectiveness of cognitive therapy in treating anxiety symptoms in adolescents.